Penanaman Karakter Anak Usia Dini melalui Pembelajaran Tari Kreatif Berbasis Ramah Anak - Wahyudi, Ayu Vinlandari; Indra Gunawan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The growth and development of early childhood is certainly supported by several aspects, such as development in cognitive, affective and psychomotor aspects. Nowadays, many cases arise due to the erosion of individual character values. Thus, every individual needs to have a good personality and character from an early age. This research aims to find out how to instill character in early childhood through child-friendly creative dance learning. This research is qualitative research with descriptive analysis methods. Data collection techniques in this research were obtained through observation, interviews and documentation. Data analysis techniques are obtained using data reduction, data verification, and data presentation. The results of this research show that dance learning has the potential to instill character in early childhood. Creative dance learning on a child-friendly basis makes it easy for young children to learn dance and develop their creativity, because through creative dance learning children are given aesthetic experiences to express and be creative through dance works. The character values that serve as a reference for cultivating character through child-friendly creative dance learning are religious values, self-confidence values, mutual cooperation values, and tolerance values.